Digitalisasi Sistem Kehadiran Pegawai melalui Penerapan Absensi Online Berbasis IoT di Kantor Desa Perian - Taufik Akbar; M.Julianto Maulana Putra; Dwi Rahayu; Ramli Ahmad; Hizbul Izzi (Universitas Hamzanwadi, 2026)
Attendance recording is an important aspect in supporting administrative effectiveness and public services within village government institutions. However, conventional attendance systems still face several limitations, including recording errors, delayed data recapitulation, and difficulties in conducting real-time attendance monitoring. This community service activity aimed to implement an Internet of Things (IoT)-based online attendance system at Perian Village Office, Montong Gading District, East Lombok Regency. The system was developed using an ESP32 microcontroller, a fingerprint sensor for user authentication, a Real Time Clock (RTC) module for timestamp recording, an OLED display for information output, and Google Sheets as a cloud-based data storage platform. The implementation method consisted of needs assessment, hardware and software design, system deployment, user training, testing, and system assistance. The results showed that the developed system was able to identify users through fingerprint authentication, automatically record attendance time, and transmit attendance data to Google Sheets in real time. All main system functions, including user enrollment, attendance recording, online data storage, and administrator management features, operated successfully according to user requirements. The implementation of this system improved the effectiveness of attendance management and supported the digital transformation of village administration through a more transparent, accurate, and efficient attendance recording process